Song and metaphoric imagery in forensic music therapy - Chambers, Carol (2008)
The present research study grew out of my professional practice as a music therapist, and seeks to put forward a new approach to the relationship between theory, research and clinical practice - while still relating in meaningful ways to a broad range of existing work. Music therapy in the UK is a broad and expanding profession, encompassing a notably diverse range of theoretical approaches and practical applications. Such approaches and applications may use, for example, free improvisation, songwriting, or listening- and response-based techniques. And there is a range of specialised literature dealing with each of these areas, as well as a number of broader, overarching studies dealing with the overall field. Within the tradition of a model based largely on musical improvisation, which has been my own practice, the use of pre-composed songs might be regarded as unusual, perhaps even as anomalous. But I hope to show that it is in fact a useful and profoundly revealing process which is firmly rooted in an ethos of active musical participation. This thesis examines the use of songs in forensic pyschiatric music therapy for women, and offers this use of song as an alternative model of musical creativity within such a context.